Price-change calculations based on 3 forms of input-output model - illustration from estimates of impact of equal pay on Irish industry - Henry, EW; Walsh, BM (Economic & Social Studies, 1971)
The official Input-Output (I-O) Tables for 1964 provide us with a 17 sector model in Appendix Tables A1, A2 and A3. In this version of the model, similar imports are distributed along the rows of the transactions matrix together with domestically produced commodities and the two flows may not be identified separately. There is, however, an aggregate subtraction of a similar import vector from the total flow aggregate vector, to yield the aggregate domestic output vector. We shall refer to this as Version 1 of the basic I-O model.
Keywords: Mathematics